The Effectiveness of the Discrimination Model in Reducing Psychological Trauma and Enhancing Informed Care Skills among Psychologists during the Gaza War - Atiya , Mai. Hassan; Awad , Hussni Mohmmad (Dirasat: Educational Sciences, 2025)
Objectives: This study aims to explore the effectiveness of the Discrimination Model in reducing trauma among psychologists and enhancing trauma-informed care skills during the Gaza war. Methods: The study employs a quasi-experimental design, with a sample of (24) male and female psychologists working in the field in Gaza. The sample was evenly divided into two groups experimental and control using a matching method. The Discrimination Model was applied to the experimental group over (16) sessions, each lasting (120) minutes. Results: The results of the study reveal statistically significant differences between the experimental and control groups on trauma scale in favor of experimental group. Additionally, statistically significant differences were found between the two groups on trauma-informed care skills scale, also favoring the experimental group. Significant differences were observed between pre-test and post-test measurements within the experimental group, with post-test results showing improvement. The program's effect size was high, reaching (83.4%) on trauma scale and (58%) on trauma-informed care skills scale. Furthermore, no significant differences were found between post-test and follow-up measurements for experimental group on both scales, indicating the sustained effectiveness of the Discrimination Model. The program's effectiveness persisted even after an eight-week follow-up period. Conclusions: The Discrimination supervisory program is effective in reducing psychological trauma among psychologists and enhancing trauma-informed care skills during the Gaza war. The study recommends implementing the Discrimination supervisory program for all psychologists in Palestine after the end of the war in Gaza.